The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/med.22002
|View full text |Cite
|
Sign up to set email alerts
|

Translating mesenchymal stem cell and their exosome research into GMP compliant advanced therapy products: Promises, problems and prospects

Chui‐Yan Ma,
Yuqing Zhai,
Chung Tony Li
et al.

Abstract: Mesenchymal stem cells (MSCs) are one of the few stem cell types used in clinical practice as therapeutic agents for immunomodulation and ischemic tissue repair, due to their unique paracrine capacity, multiple differentiation potential, active components in exosomes, and effective mitochondria donation. At present, MSCs derived from tissues such as bone marrow and umbilical cord are widely applied in preclinical and clinical studies. Nevertheless, there remain challenges to the maintenance of consistently goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 113 publications
0
2
0
Order By: Relevance
“…52 In addition, specialised stem cell banks exist to collect, preserve and distribute various stem cell types for research, medical and therapeutic purposes, adhering to ethical and regulatory standards. 53 The availability of stem cells is influenced by sourcing methods, ethical considerations and regulatory frameworks, with ongoing technological advancements continually refining the collection, storage and application processes for enhanced prospects in medical research and treatment. 53 Enhanced endogenous neurogenesis and angiogenesis poststroke have been shown to significantly enhance neurofunctional recovery; our related work on NAMPT also had similarly substantiated this claim.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…52 In addition, specialised stem cell banks exist to collect, preserve and distribute various stem cell types for research, medical and therapeutic purposes, adhering to ethical and regulatory standards. 53 The availability of stem cells is influenced by sourcing methods, ethical considerations and regulatory frameworks, with ongoing technological advancements continually refining the collection, storage and application processes for enhanced prospects in medical research and treatment. 53 Enhanced endogenous neurogenesis and angiogenesis poststroke have been shown to significantly enhance neurofunctional recovery; our related work on NAMPT also had similarly substantiated this claim.…”
Section: Open Accessmentioning
confidence: 99%
“…53 The availability of stem cells is influenced by sourcing methods, ethical considerations and regulatory frameworks, with ongoing technological advancements continually refining the collection, storage and application processes for enhanced prospects in medical research and treatment. 53 Enhanced endogenous neurogenesis and angiogenesis poststroke have been shown to significantly enhance neurofunctional recovery; our related work on NAMPT also had similarly substantiated this claim. 1 54-56 Numerous preclinical trials have demonstrated that stem cell transplantation after stroke can improve neurogenesis, synaptogenesis and angiogenesis in the brain, leading to functional recovery.…”
Section: Open Accessmentioning
confidence: 99%
“…The generation, surface protein expression and content composition of sEVs are influenced by cell development conditions and the culture medium formulation. 130 Maintaining consistent cell growth ensures extracellular vesicle stability, uniformity, and efficacy. Furthermore, it should be noted that storage conditions might influence the size distribution of sEVs and the stability and biodistribution of cells.…”
Section: The Future Prospectivementioning
confidence: 99%
“…MSCs are attractive cell sources in regenerative medicine based on their abilities to self-renew and differentiate into mesenchymal tissue lineage [137]. During the last few years, the use of MSCs and their cell-free derivatives has seen an increasing number of applications in disparate medical fields, including chronic musculoskeletal conditions [138][139][140][141][142]. All of these approaches would require cell harvesting and transplantation.…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%